A cross-sectional study comparing the expression of DNA repair molecules in subjects with and without atherosclerotic plaques - Arapi, Berk; Unal, Selin; Malikova, Narmina; Omeroglu, Suat Nail; Guven, Mehmet (Molecular biology reports, 2024)
Background Atherosclerosis, serving as the primary pathological mechanism at the core of cardiovascular disease, is now widely acknowledged to be associated with DNA damage and repair, contributing to atherosclerotic plaque formation. Therefore, molecules involved in the DNA repair process may play an important role in the progression of atherosclerosis. Our research endeavors to explore the contributions of specific and interrelated molecules involved in DNA repair ( APE1 , BRCA1 , ERCC2 , miR-221-3p , miR-145-5p , and miR-155-5p ) to the development of atherosclerotic plaque and their interactions with each other. Methods & results Gene expression study was conducted using the real-time polymerase chain reaction (qRT-PCR) method on samples from carotid artery atherosclerotic plaques and nonatherosclerotic internal mammary arteries obtained from 50 patients diagnosed with coronary artery disease and carotid artery disease. Additionally, 50 healthy controls were included for the determination of 8-hydroxy-2’-deoxyguanosine (8-OHdG). Although no difference was observed in mRNA gene expressions, we noted a decrease in miR-155-5p gene expression ( p = 0.003) and an increase in miR-221-3p gene expression ( p = 0.015) in plaque samples, while miR-145-5p gene expression remained unchanged ( p = 0.57). Regarding serum 8-OHdG levels, patients exhibited significantly higher levels (1111.82 ± 28.64) compared to controls (636.23 ± 24.23) ( p < 0.0001). Conclusions In our study demonstrating the role of miR-155-5p and miR-221-3p in atherosclerosis, we propose that these molecules are potential biomarkers and therapeutic targets for coronary artery diseases and carotid artery disease.